Factors Generating the Willingness of Romanian Consumers to Buy Raw Milk from Vending Machines - Marius Mircea Sabău; Pompei Mititean; Cristina Bianca Pocol; Dan-Cristian Dabija (Foods, 2023)
The use of automatic raw milk dispensers for products obtained from Romanian farms can represent an effective method of encouraging the development of short supply chains and promoting sustainable production and consumption systems. There are very few studies in the literature, especially in emerging economies, that analyze consumer perception regarding the use of raw milk dispensers; most of the research is focused on technical aspects regarding how such machines function and food safety, and less on consumers’ perceptions towards them or consumer satisfaction, loyalty, or intention to use them. Therefore, the objective of this research was to investigate the willingness of Romanian consumers to buy raw milk from vending machines. In this regard, the authors drew a conceptual model to assess the factors that trigger willingness to buy raw milk from vending machines and then implemented a quantitative-based survey among Romanian consumers who buy raw milk from vending machines. The data were analyzed by modeling structural equations with SmartPLS. The results reveal that the generation of consumer willingness to buy raw milk from vending machines depends on how consumers perceive raw milk but also on the product safety, reusability of the milk bottle, and the provenance of the raw milk, as well as the nutritional qualities of the unprocessed raw milk. The paper extends previous studies based on the stimulus–organism–response (SOR) and deepens the understanding of consumers’ perception towards raw milk dispensers. Furthermore, the results also highlight possible managerial strategies that aim to improve the understanding of consumers.